Utilizing the Use of Google Trends to Discover The Architectural Attractiveness of a Place in Indonesia - Onie Dian Sanitha; Novera Kristianti; Theo Fransisco; Yunida Iashania (Journal of Artificial Intelligence in Architecture, 2023)
A person's memory of the image of a place is powerful, which is influenced by a uniqueness supported by continuity of information. Every visitor's image will be very subjectively evaluated through the internet information media. The challenge lies in subjective perception through internet media information which only sometimes leads to real quality due to perceptions formed from the continuity of information received. A shift in meaning allegedly led to a phenomenon of similar motivation between video game users and traveling for healing purposes. From the perspective of a Google search, the word "traveling" refers to buildings and places with ecological and natural concepts. Meanwhile, video games also offer a natural concept but are more competitive. Using Google Trends, this study attempts to formulate city popularity data using the keyword "traveling." Natural Ecology is the highest choice for social media users, and "healing" is the primary motivation. The value of natural architectural instruments can be a focus to support a sustainable development process for a place based on the popularity of today's needs.